Poder, comunidades campesinas e industria minera: el gobierno comunal y el acceso a los recursos en el caso de Michiquillay* - Burneo, María Luisa (2010)
This paper analyzes changes in community governance in the contextof negotiations with a mining company. We focus on three issues:the role played by the community government on the regulation ofcommunity resources and territory, the diverse and complex intereststhat emerge in the presence of mining activity; and, the communityas a political institution confronting external pressures over its land.We develop a study case focusing on the negotiation process betweenthe Michiquillay peasant community and Anglo American MiningCompany in Cajamarca, Peru. This information was obtained doingfieldwork in the community in 2009. In our analysis we observe thatchanges on community resources regulation, its uses and valorization,as well as changes on the balance of power between economicand political actors, have created a greater level of complexity in thecommunity, creating new levels of community decision and spaces fordisputing resources’ control. At the same time, new inter communalconflicts emerge and fragmentation of community lands increases.In this context the community as an institution plays a central rolein the negotiation process over access productive resource and thedistribution of financial capital.